STATISTICAL EVALUATION OF FOUR-PARAMETER MOISTURE SORPTION ISOTHERM MODELS - Mitrevski, Vangelče (Journal on Processing and Energy in Agriculture, 2020)
In the scientific and engineering literature, there are various mathematical methods for modelling the equilibrium moisture content of agricultural and food materials. The objective of the present study was to statistically evaluate a total of thirty-two four-parameter moisture sorption isotherm models and subsequently compare their goodness of fit. The moisture sorption isotherm models considered were either originally developed or taken from the reference literature. The coefficient of determination and the graphical evaluation of residual randomness were utilized as the main assessment criteria for statistical evaluation of the moisture sorption isotherm models examined. The statistical performance of the models was tested according to the equilibrium moisture content of quinces. On the basis of the statistical analyses performed, the Popovski&Mitrevski model, i.e. the model with the reference numbers M25 and M30, and the McLaren&Rowen model were found to have the best statistical performance of all the models considered.
Keywords: sorption isotherms, four parameters model, statistical evaluation